(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This chapter consists of the background of the study, Related literature, Related studies in thematic approach, Relevance of the Review of Related Literature and Studies to the present happening, Theoretical Framework, Conceptual Framework, Statement of the Problem, Assumption, Scope, and Delimitation of the study, Significance of the study, and definition of terms. To complete this study properly, it is necessary to analyze the data collected and answer the research questions. As already indicated in the preceding chapter, data is interpreted in a descriptive form. This chapter discusses the interpretations of the data gathered by the researchers. This chapter will show the procedure of reviewing data and drawing pertinent conclusions utilizing a variety of analytical techniques. The researchers can categorize, manipulate, and summarize data with the aid of interpretation to find answers to important issues. This chapter presented the summary of findings, conclusion, and recommendation formulated by the researchers. This study focused on The Role of Social media in Preventing Cyber Fraud at Barangay 165 Bagbaguin Caloocan city. The respondents are 40 Residents, and 10 Law Enforcement agencies participated during the data-gathering phase. It focused on the following: 1) Demographic profile of the respondents. 2) Respondents assess the Role of Social media in Preventing Cyber Fraud at Barangay 165 Bagbaguin Caloocan city. In terms of compromise, cyber scams, and information. 3) Problems encountered by the respondents in Barangay 165 Bagbaguin Caloocan city. 4) Measure that may be proposed to address the problems encountered by Barangay 165 Bagbaguin Caloocan city in Preventing Cyber fraud. The statistical tools used were frequency and percentage, weighted mean, ranking, and Likert Scale.